2003
DOI: 10.5194/acp-3-417-2003
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric measurements of gas-phase HNO<sub>3</sub> and SO<sub>2</sub> using chemical ionization mass spectrometry during the MINATROC field campaign 2000 on Monte Cimone

Abstract: Abstract. The EU-project MINATROC (MINeral dust And TROpospheric Chemistry) aims at enabling an estimation of the influence of mineral dust, a major, but to date largely ignored component of tropospheric aerosol, on tropospheric oxidant cycles. Within the scope of this project continuous atmospheric measurements of gas-phase HNO 3 and SO 2 were conducted in June and July 2000 at the CNR WMO station, situated on Monte Cimone (MTC) (44 • 11 N -10 • 42 E, 2165 m asl), Italy. African air transporting dust is occas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
66
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(67 citation statements)
references
References 55 publications
1
66
0
Order By: Relevance
“…The autumn maximum could be attributed to the high number of samples originating from Mediterranean region (see later, section III.5.1). In the PM 10-1 , it is bound with alkaline sea salt and/or mineral dust particles (Harrison and Kitto 1990;Pakkanen et al 1996;Hanke et al 2003;Krueger et al 2004;Sullivan et al 2007). The reaction of HNO 3 to sea salt has been pointed out in several publications (Robbins et al 1959;Martens et al 1973;Harrison and Pio 1983;Pakkanen et al 1996;Plate and Schulz 1997;Vignati et al 2001;Sørensen et al 2005), resulting in a loss of Cl -relative to the Cl -/Na + ratio in the sea composition.…”
Section: Pm 10-1mentioning
confidence: 99%
“…The autumn maximum could be attributed to the high number of samples originating from Mediterranean region (see later, section III.5.1). In the PM 10-1 , it is bound with alkaline sea salt and/or mineral dust particles (Harrison and Kitto 1990;Pakkanen et al 1996;Hanke et al 2003;Krueger et al 2004;Sullivan et al 2007). The reaction of HNO 3 to sea salt has been pointed out in several publications (Robbins et al 1959;Martens et al 1973;Harrison and Pio 1983;Pakkanen et al 1996;Plate and Schulz 1997;Vignati et al 2001;Sørensen et al 2005), resulting in a loss of Cl -relative to the Cl -/Na + ratio in the sea composition.…”
Section: Pm 10-1mentioning
confidence: 99%
“…The phenomena of low O 3 and high dust concentrations have been observed in the field (e.g., Bonasoni et al 1997;Prospero et al 1995). As part of the Mineral Dust and Tropospheric Chemistry (MINATROC) project, which was an intensive field measurement campaign conducted at CMN from June 1 to July 5, 2000 (Balkanski et al 2003;Bauer et al 2004;Bonasoni et al 2004;de Reus et al 2005;Fischer et al 2003;Gobbi et al 2003;Hanke et al 2003;Putaud et al 2004;Van Dingenen et al 2005) and at IZO from July 15 to August 15, 2002(de Reus et al 2005Salisbury et al 2006;Umann et al 2005). Their aim was to fully characterize gas and aerosol species with a complete set of measurements in order to identify the heterogeneous reactions of dust.…”
Section: Dust and Volcanic Emissionsmentioning
confidence: 99%
“…Putaud et al (2004) suggested that NO 3 − was shifted toward the aerosol super-μm fraction in the presence of dust. Hanke et al (2003) and Umann et al (2005) observed an efficient uptake of gaseous HNO 3 by mineral dust aerosol particles, thereby suggesting that mineral dust might be a significant sink for HNO 3 in the troposphere. Hence, it could affect the photochemical cycles and O 3 production.…”
Section: Dust and Volcanic Emissionsmentioning
confidence: 99%
“…CIMS techniques provide generally a high time resolution (∼1 s) in combination with low detection limits in the range of a few pmol mol −1 . CIMS was originally introduced in atmospheric research by Arnold et al (1978) and now is established as a powerful method for the measurement of a series of trace gases (Kiendler et al, 2000;Neuman et al, 2000;Nowak et al, 2002;Thornton et al, 2002;Hanke et al, 2003;Slusher et al, 2004;Speidel et al, 2007;Kercher et al, 2009), for a recent review see for example Huey (2007).…”
mentioning
confidence: 99%